(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the needs, describe the development process, and determine the feasibility of e-card-based emotion map media as a Guidance and Counseling (BK) service medium for junior high school students. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Media development was carried out through validation by information technology experts and BK media experts, as well as limited trials with BK teachers and junior high school students. Data were collected using validation questionnaires and user response questionnaires, then analyzed descriptively quantitatively. The results showed that the e-card-based emotion map media obtained the "Very Good" category based on expert and user assessments. This media was considered interesting, easy to use, and able to help students recognize, understand, and reflect on their emotional experiences. Thus, the e-card-based emotion map media is suitable for use as a supporting medium for Guidance and Counseling services at the junior high school level to facilitate the development of students’ emotional awareness and reflection.